2004
DOI: 10.1074/jbc.m405747200
|View full text |Cite
|
Sign up to set email alerts
|

Induced Inhibition of Ischemic/Hypoxic Injury by APIP, a Novel Apaf-1-interacting Protein

Abstract: We describe the isolation and characterization of a new apaf-1-interacting protein (APIP) as a negative regulator of ischemic injury. APIP is highly expressed in skeletal muscle and heart and binds to the CARD of Apaf-1 in competition with caspase-9. Exogenous APIP inhibits cytochrome c-induced activation of caspase-3 and caspase-9, and suppresses cell death triggered by mitochondrial apoptotic stimuli through inhibiting the downstream activity of cytochrome c released from mitochondria. Conversely, reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
58
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 39 publications
(26 reference statements)
4
58
1
Order By: Relevance
“…These distinct activities seem to be assigned to different domains of APIP. As shown in the previous report (Cho et al, 2004), core domain of APIP spanning the common region of APIP and APIP2 was sufficient to suppress etoposide-induced cell death. However, the C-terminal region of APIP rather than core domain is required for the activation of ERK1/2 during hypoxia (Figure 1e).…”
supporting
confidence: 68%
See 3 more Smart Citations
“…These distinct activities seem to be assigned to different domains of APIP. As shown in the previous report (Cho et al, 2004), core domain of APIP spanning the common region of APIP and APIP2 was sufficient to suppress etoposide-induced cell death. However, the C-terminal region of APIP rather than core domain is required for the activation of ERK1/2 during hypoxia (Figure 1e).…”
supporting
confidence: 68%
“…Our previous work showed that APIP binds to Apaf-1 and inhibits the intrinsic cell death, postulating that the antiapoptotic activity of APIP lies in its binding ability to Apaf-1 (Cho et al, 2004). From subsequent analyses, however, we observed that the overexpression of APIP further suppressed hypoxia-induced death of Apaf-1(À/ À) mouse embryonic fibroblasts (MEF) cells (Supplementary data Figure 3).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The association of rs514182 with pyroptosis was surprising, because APIP was previously identified as an inhibitor of a different cell death pathway, the intrinsic (caspase-9-dependent) apoptotic pathway (31). Apoptosis can be induced in LCLs by pharmacologic agents, such as the chemotherapeutic drug carboplatin (20,32).…”
Section: Resultsmentioning
confidence: 99%